2021
DOI: 10.1108/jiabr-03-2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motivating language and management effectiveness: empirical evidence from Waqf institutions in Malaysia

Abstract: Purpose This study aims to extend the investigation on leader communication by assessing the usage of motivating language (ML) by leaders in Waqf institutions in Malaysia. Design/methodology/approach Data analysis was carried out using structural equation modelling via the partial least squares. The probability sampling technique was deemed more suitable for this study as the available data was definable for constructing the sampling frame. Findings Management effectiveness was shown to have a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the confidence interval values do not show a value of 1 in any of the constructs, except for GDRP and inflation, which were a single observation. Thus, the constructs meet the HTMT criteria, fulfilling discriminant validity (Sharip et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the confidence interval values do not show a value of 1 in any of the constructs, except for GDRP and inflation, which were a single observation. Thus, the constructs meet the HTMT criteria, fulfilling discriminant validity (Sharip et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…They found that human capital, structural capital and spiritual capital impact organisational performance but not waqf institutions. Meanwhile, Sharip et al (2022) discussed the effectiveness of management and leadership style through motivation in waqf institutions. The similarity of these two studies is that they discuss the management of waqf institutions as non-profit organisations for the institution's sustainability.…”
Section: Citation Analysismentioning
confidence: 99%
“…Thus, waqf institutions can formulate various innovations and development of waqf management systems following Islamic sharia. Sharip et al (2022) used the motivating language (ML) of the leaders of waqf institutions in Malaysia to achieve this. However, Sharip et al (2022) failed to deliver the research findings as their findings cannot be considered a comprehensive solution to improve management effectiveness in waqf institutions.…”
Section: Research Agenda 4: the Effectiveness Of Waqf Management In M...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, waqif endows land for cemeteries or endows land for the poor. Thus, in a special waqf, the trustee must carry out the purpose of the waqf that has been made (Sharip et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%